Three new species of the genus Xenolecanium Takahasi (Hemiptera: Coccomorpha: Coccidae), with an updated generic diagnosis and key to species - Hodgson, Chris J. (Zootaxa, 2022)
Among the scale insect slide mounts deposited in the Natural History Museum, London, U.K. are several that were originally collected by the late Ryoichi Takahashi. These include slides of three previously undescribed species of Xenolecanium (Coccidae: Coccomorpha), each given a manuscript name by Takahashi. These species are here formally described and illustrated: X. ryoichii Hodgson sp. nov., X. maritimum Hodgson sp. nov. and X. pendleburyi Hodgson sp. nov. A revised generic diagnosis and a key to the five species now known in Xenolecanium is included.